The Effect Of Gallery Walk Techniques On Students’ English Writing Ability In Report Texts - Azhary Tambusai, Suci Adiany, (Invention: Journal Research and Education Studies, 2021)
The objective of this research was to find out the effect of that gallery walk technique on students’ English writing ability in report texts at the tenth grade students of SMA Swasta Baitul Aziz Bandar Klippa. The type of research was quantitative research and it was conducted by using experimental design with two classes, in experimental class consisted of 23 students and control class consisted of 27 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by writing test. The data were analyzed by using t-test formula. The result of the data showed that tobserve (6.55) value was higher than the ttable in which tobserve>ttable (6,55>1,67). The finding showed that the hypothesis was accepted. It means that there was a significant effect of gallery walk technique on students’ English writing ability in report texts at SMA Swasta Baitul Aziz Bandar Klippa Academic Year 2021/2022.